Shape Memory Polymers and Shape Memory Polymer Composites stimulated by 5 Stimuli Types - SUNGSEE, PASUTA (Science Essence Journal, 2020)
Shape memory polymers (SMPs) and shape memory composites (SMPCs) are materials recovered by external stimulations and contain important components which are stable network and reversible switching transition [1]. This review explains stimulation mechanism, shape recovery and mechanical properties of SMPS and SPMCs induced by temperature, Infrared-light, magnetic field, electrical field and chemical. The previous research works reported the synergistic effect of boron nitride/carbon nanotube and excellent properties of thermally reduced graphite oxide which were the reinforcement in epoxy-based SMP stimulated by temperature and infrared-light, respectively. Ferromagnetic shape memory alloys and modified carbon nanotubes were used as a filler in epoxy-based SMPC induced by magnetic field and polyurethane/poly (lactic acid)-based SMPC induced by electrical field, respectively. The dispersion of fillers in polymer matrix and filler-matrix interaction affect to shape recovery and mechanical properties. Shape memory effect of SMPCs stimulated by temperature, infrared-light and electrical field depends on thermal conductivity, and shape recovery of SMPs stimulated by chemical depends on chemical structure change.